Critical realism and education policy analysis in conflicts and crises: towards conceptual methodologies. Issue 6 (18th August 2022) - Couch, Daniel
ABSTRACT: This paper considers the utility of critical realism as an ontological foundation for the analysis of education policy in emergencies. By exploring the synergy between critical realism and a method to analyse policy known as Critical Policy Analysis, the paper argues for the use of conceptual analytical tools when examining education policy in conflict-affected contexts. It illustrates the value of theory-informed analysis by reflecting on a recent study of Afghanistan's higher education strategic planning, and advocates for critical engagement with broader cultural, political, and economic factors in the analysis of education policies during conflicts and crises.